Odonata as Indicators? Dragonflies and Damselflies Respond to Riparian Conditions along Ozark Spring Streams - Cameron R. Cheri; Debra S. Finn (Hydrobiology, 2023)
The Odonata are not typically regarded as informative taxa for stream bioassessment in North America compared to other insects, particularly when monitoring the ecological impacts of organic pollution. However, we hypothesized that stream-dwelling odonates are useful bioindicators of riparian conditions because vegetation associated with streams is used for oviposition and establishing breeding territories and is likely a cue for a suitable nymphal habitat. We sampled odonates from multiple microhabitats and all macroinvertebrates from riffle habitat in 12 Ozark Highlands (USA) spring streams along a gradient of riparian conditions. We also measured a standard suite of physical and chemical variables in each stream. We compared various aspects of the odonate and riffle macroinvertebrate assemblages among sites to evaluate sensitivity to variables associated with riparian structure compared to the other physical and chemical variables measured. The odonates were strongly associated with riparian-specific variables, while riffle macroinvertebrates were associated with riparian variables to a lesser degree. The additional environmental variables explained minimal variation in either assemblage. Overall, our results suggest that Odonata alone could be useful for biomonitoring associated with riparian structure around Ozark spring streams. The sensitivity of odonates to riparian conditions in other Nearctic regions should be further studied to identify regional and species-specific differences.